VA opsin, melanopsin, and an inherent light response within retinal interneurons. - Jenkins, A; Muñoz, M; Tarttelin, E; Bellingham, J; Foster, R; Hankins, M (2003)
BACKGROUND: Although photoreception is best understood in rods and cones, it is increasingly clear that these are not the only photoreceptive cells of the vertebrate retina. While considerable attention has been paid to the role of melanopsin in the generation of intrinsic light sensitivity in the retinal ganglion cells of mammals, nothing is known about the photoreceptive capacity of the horizontal cells of the fish retina in which both VA opsin and melanopsin are expressed. As yet, there has been little more than speculation as to the physiological function of these opsins within local retinal circuit neurons. RESULTS: VA opsin and melanopsin have been isolated and localized within the well-characterized cyprinid retina of the roach (Rutilus rutilus). Parallel electrophysiological studies identified a novel subtype of horizontal cell (HC-RSD) characterized by a depolarizing response that fits an opsin photopigment with a lambda(max) of 477 nm. The HC-RSD cells mediate responses to light that are characterized by long integration times, well beyond those observed for rods and cones. Significantly, HC-RSD responses persist when the conventional photoreceptor inputs are saturated by background light. CONCLUSIONS: The syncytium of coupled horizontal cells has long been considered to provide a signal of overall retinal irradiance. Our data suggest that this light information is, at least in part, derived from a population of intrinsically photosensitive VA opsin and/or melanopsin horizontal cells.